2019
DOI: 10.1088/1361-648x/ab55f4
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic vortex beams in synthetic magnetic fields

Abstract: We analyze propagation of acoustic vortex beams in longitudinal synthetic magnetic fields. We show how to generate two field configurations using a fluid contained in circulating cylinders: a uniform synthetic magnetic field hosting Laguerre-Gauss modes, and an Aharonov-Bohm flux tube hosting Bessel beams. For non-paraxial beams we find qualitative differences from the well-studied case of electron vortex beams in magnetic fields, arising due to the vectorial nature of the acoustic wave's velocity field. In pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Also, considering the vector effect [24] in the extinction. Several interesting acoustic scattering problems as spin propagation [44], orbital angular momentum [45], vortex modes in synthetic fluids [46], evanescent Bessel waves [47] could be studied using LW. This method can suit to study experimentally new structured beams, such as carving beams recently reported [48].…”
Section: Discussionmentioning
confidence: 99%
“…Also, considering the vector effect [24] in the extinction. Several interesting acoustic scattering problems as spin propagation [44], orbital angular momentum [45], vortex modes in synthetic fluids [46], evanescent Bessel waves [47] could be studied using LW. This method can suit to study experimentally new structured beams, such as carving beams recently reported [48].…”
Section: Discussionmentioning
confidence: 99%
“…This work was motivated by recent strong interest in (i) polarization Möbius strips in 3D polarized optical fields [27][28][29][30][31][32][33][34][35][36] and (ii) vectorial spin properties of acoustic and water-surface waves [4][5][6][7][8][9][10][11][12]. We have shown that these research directions can be naturally coupled, and that polarization singularities, such as C-points and polarization Möbius strips, are ubiquitous for inhomogeneous (yet monochromatic) acoustic and water-surface waves.…”
Section: Discussionmentioning
confidence: 99%
“…where k = k/𝑘, k is the wavevector, 𝑘 = 𝜔/𝑐 is the wavenumber, 𝑐 = 1/ √ 𝜌𝛽 is the speed of sound, and 𝑃 0 = √︀ 𝜌/𝛽 𝑉 0 . Sound waves are longitudinal because V ‖ k, but still have a vector nature described by the velocity field V [4,[6][7][8][9][10]. In what follows, we will focus on the polarization properties of this vector wave field: the real velocity field 𝒱(r, 𝑡) at a given point r traces a polarization ellipse.…”
Section: Polarization Singularities In a 2d Acoustic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete review of the theoretical foundations for the acoustic and electromagnetic field theory has also been reported [12]. Applications in acoustic plasmon propagation in waveguides making analogies with electromagnetic fields [13], acoustic surface waves [14], acoustic radiation forces [15,16,17,18,19], enhanced manipulation in near fields [20], in fluids physics propagating vortex [21], in inhomogeneous media [22] using meta-surface waveguides have been demonstrated applications on spinrelated robust transport [23], and the importance to explore symmetry properties to enhanced acoustic propagation in the near field [24].…”
Section: Introductionmentioning
confidence: 99%